Understanding the Efficiency of Splenic Hemangiosarcoma Diagnosis Using Monte Carlo Simulations. Issue 6 (November 2019) - Herman, Eric J.; Stern, Adam W.; Fox, Richard J.; Dark, Michael J.
Hemangiosarcoma is a common neoplasm of the spleen in older dogs. However, diagnosis is complicated by necrosis and hemorrhage, which can mimic a number of benign processes. Currently, there is no consensus about the number of sections pathologists should examine to rule out hemangiosarcoma. To answer this question, we examined 413 histopathologic sections from 50 cases of canine hemangiosarcoma (mean: 8.1 sections per case; range, 5–14). Each section had the presence or absence of hemangiosarcoma determined by 2 board-certified anatomic pathologists. Then, 100 Monte Carlo simulations were performed, randomly selecting sections from each case 10 000 times and the results averaged. These simulations suggest that examination of 5 sections from a spleen with hemangiosarcoma yields a 95.02% chance of diagnosing hemangiosarcoma, while examination of 10 sections yields a 98.59% chance of diagnosis when hemangiosarcoma is in fact present. The data emphasize the need to submit the entire spleen for histopathologic examination in suspected cases of hemangiosarcoma and suggest that 5 sections obtained by a trained individual are likely sufficient for diagnosis.